Pengaruh Pendapatan Asli Daerah, Dana Perimbangan dan Belanja Daerah terhadap Indeks Pembangunan Manusia di Provinsi Sumatera Utara - Dewi Mahrani Rangkuty; Mohammad Yusuf; Rothsalina Agustia Pasaribu (Universitas Negeri Padang, 2022)
The study aims to test the influence of local native income, balanced funds, and regional spending on the human development index. The method used is multiple linear analysis. This type of quantitative research uses secondary data on local government financial statements that have been audited by the CPC and statistical data from www.bps.go.id. The study sample criteria cover all 33 Regencies / Cities of North Sumatra in 2018-2019 with SPSS version 20. The results showed that the original income of the region, the balance fund affected the human development index. In comparison, regional spending did not significantly affect the human development index. Simultaneously the original income of the region, balanced funds, and provincial spending are jointly influential on the human development index of North Sumatra province. Every government in North Sumatra province is expected to increase investment in the physical form further so that fixed assets increase every year. With increased means, it can support the economic welfare of the community